Search for security - "Field, M J" (London, 1960)
The romantic figure of the Noble Savage- gloriously glowing in rude but radiant physical health- was quickly banished into the realm of myth when Physical Medicine revealed that it was hardly possible to find in a primitive community any healthy person. Malaria, yaws, deficiency diseases, worms and other parasites were the basic burden which virtually every rural African had to learn to carry before he shouldered the additional economic and social demands of life.
Keywords: Psychology